Investment analysis & portfolio management - Frank K. Reilly (Cengage Learning, 2024)
The 11th edition's unparalleled international coverage provides specific information on non-U.S. markets, instruments, conventions and techniques. New detailed discussions explain the impact of changes in both technology and regulations on global security markets. In addition, three chapters are devoted to derivatives securities--which are now standard investment instruments.